Analysis of binder proportions on the calorific value in a briquette made from cocoa pod husk in the Peruvian Amazon - Solórzano, Richard; Paquiyauri, Alexandra; Neyra, Walter; Siqueira-Bahia, Rita de Cassia; Vallejos-Torres, Geomar (Frontiers in Energy Research, 2025)
IntroductionThe growing global demand for fuel has created challenges in the supply of raw materials, positioning biomass derived from cocoa pod husk waste as an economically viable and environmentally sustainable energy alternative.MethodsThis study evaluated the effect of different binder types on the calorific value of briquettes produced from fermented cocoa pod husk waste in the Peruvian Amazon. For the calorific value assay, 1.05 kg of fermented cocoa pod husk waste was combined with 100 g of starch-based binders derived from corn, cassava, or potato, all sourced from the San Martín region. Statistical analyses were performed in R Studio using the dplyr package, and mean comparisons were conducted with Tukey’s HSD test (p < 0.05).ResultsThe lowest ash content was obtained with the potato-starch binder (7.03%), whereas the highest value was recorded in the control treatment without binder (8.71%). Fixed carbon content ranged from 3.70% to 5.97% across treatments. The lowest calorific value was observed with the corn-starch binder (3,486.0 kcal/kg), while the highest was achieved with cassava starch (3,586.66 kcal/kg).DiscussionThese findings demonstrate the technical feasibility of producing high-quality charcoal briquettes from cocoa pod husk waste using starch-based binders, providing a sustainable alternative to conventional fuels.